Bandotan (Ageratum conyzoides L.) as Bio-Fungicide for Controlling Fusarium oxysporum in Chili (Capsicum annuum L.) - Agustrina, Rochmah; Fadhilla, Nurul; Tamara, Derlian Ella; Chrisnawati, Lili; Yulianty, Yulianty; Mahfut, Mahfut (Jurnal Biodjati, 2024)
Fusarium oxysporum L. is a fungus responsible for causing plant wilt disease in various horticultural crops. Meanwhile, Bandotan (Ageratum conyzoides L.) is commonly known as a weed that contains secondary metabolites with antifungal activity. Therefore, this study aimed to determine the effect of Bandotan stem and leaf extract on the growth of Fusarium oxysporum in chili (Capsicum annuum L.) infected during the germination phase. Evaluation of stem and leaf extract was carried out separately using a one-factor Complete Randomized Design (CRD). A total of four experimental units were used consisting of C+ (sprouts not infected with Fusarium sp. and not given stem or leaf of Bandotan extract), C- (sprouts infected with Fusarium sp. but not given stem or leaf of Bandotan extract), T1 (sprouts soaked with stem or leaf of Bandotan extract and infected with Fusarium sp.), and T2 (sprouts infected with Fusarium sp., and given stem or leaf of Bandotan extract). Each experimental unit was repeated five times, and parameters observed included disease severity, as well as dry and wet weight. The results showed that based on ANOVA test at the 5% significance level, the administration of 60% dry Bandotan stem extract to chili sprouts before Fusarium sp. infection significantly reduced disease severity. However, when the treatment was carried out after sprouts were infected, disease severity was not reduced. The administration of Bandotan leaf extract to sprouts both before and after being infected with Fusarium sp. reduced disease severity but a decrease in dry weight was also observed